ENGLISH SPEAKING ANXIETY AMONG INDONESIAN JUNIOR HIGH SCHOOL STUDENTS: UNVEILING CAUSES AND SOLUTIONS - Marpaung, Nisya Rahmaini; Fithriani, Rahmah (TELL - US JOURNAL, 2023)
An important aspect that may hinder a foreign language learning is anxiety. This qualitative study attempts to examine the phenomena of speaking anxiety and clarify its causes and treatments. Thirty junior high school students of grade IX (nine) participated in this study. Interviews and Foreign Language Classroom Anxiety Scale (FLCAS) questionnaires were used to collect the data. The findings of this study reveal that the anxiety the students experience when speaking English falls into three distinct categories: low, moderate, and high, with the majority of the students had a high level of anxiety. Furthermore, it was also found that a lack of provisions and preparations to learn English, the fear of making pronunciation and grammatical errors, and feeling insecure around interlocutors who are more proficient in the language are the factors that cause students to feel anxious when speaking English.. In light of the findings of this study, students should continue to practice speaking English, attempt to reduce feelings of insecurity, maintain a positive outlook, and improve their drive to learn to speak English.